Origin of the magnetic transition at 100 K in ε-Fe2O3 nanoparticles studied by x-ray absorption fine structure spectroscopy. (8th November 2017) - López-Sánchez, J; Muñoz-Noval, A; Castellano, C; Serrano, A; del Campo, A; Cabero, M; Varela, M; Abuín, M; de la Figuera, J; Marco, J F; Castro, G R; Rodríguez de la Fuente, O; et al.
Abstract: The current study unveils the structural origin of the magnetic transition of the ε -Fe2 O3 polymorph from an incommensurate magnetic order to a collinear ferrimagnetic state at low temperature. The high crystallinity of the samples and the absence of other iron oxide polymorphs have allowed us to carry out temperature-dependent x-ray absorption fine structure spectroscopy experiments out. The deformation of the structure is followed by the Debye–Waller factor for each selected Fe–O and Fe–Fe sub-shell. For nanoparticle sizes between 7 and 15 nm, the structural distortions between the Fete and Fe-D1oc sites are localized in a temperature range before the magnetic transition starts. On the contrary, the inherent interaction between the other sub-shells (named Fe–O1, 2 and Fe–Fe1) provokes cooperative magneto-structural changes in the same temperature range. This means that the Fete with Fe-D1oc polyhedron interaction seems to be uncoupled with temperature dealing with these nanoparticle sizes wherein the structural distortions are likely moderate due to surface effects.